SAR Design with IFC - TÜRKYILMAZ, EMRAH; YAZICI, GÖKHAN (Crc Press-Taylor & Francis Group, 6000 Broken Sound Parkway Nw, Ste 300, Boca Raton, Fl 33487-2742 Usa, 2009)
This paper reports a study where IFC based building models were utilized in the evaluation of "adaptability" issues of dwelling layouts in an educational context. The first part of the study discusses a workshop on the CAD implementation of the SAR design methodology, which was popularized in Netherlands in the post-WW2 era, to increase the adaptability of residential dwellings. The second part of the study focuses on the use of IFC based building models to automate the preparation of the SAR taxonomy explained in the workshop. The primary objective of using IFC in this study was to explore the potential use of this maturing technology in design research education.